Analisis dan Perbaikan Antarmuka Pada Situs Web Brawijaya Information Technology Services (BITS) Menggunakan Metode Evaluasi Heuristik - Rendra Trihardo; Retno Indah Rokhmawati; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
UPT TIK is a BITS website manager. One that can not be separated from the quality of a website is the user interface. The website interface is very influential on the operational process of website usage. To explore the problems on the BITS website then observations and interviews conducted with related parties of BITS website manager. Based on observations and interviews, a number of problems on the BITS website interface were found. Given the importance of website function for operational activities and based on existing problems, the researcher proposes evaluation of BITS website using heuristic evaluation. Evaluation is done in 2 stages, that is early stage evaluation and final evaluation. In the early evaluation, evaluation was done on the BITS website with a total of 28 problems and the most common problems were found in the H8 category (aesthetic and minimalist design). Based on the results of the early stage evaluation of BITS website was improved. In the final evaluation, the evaluation was done on the result of BITS website improvement with the total problems of 15 were found and the most common problems found in the final evaluation lies in the category of H8 (aesthetic and minimalist design). The average of severity ratings on the final evaluation is on the scale of 2 (minor usability problem), so that sustainable improvement for the BITS website is needed.